Analisis Potensi Unggulan Dan Daya Saing Sub Sektor Pertanian, Kehutanan Dan Perikanan di Provinsi Aceh - Maliani, Tera; Nurlina, Nurlina; Andiny, Putri (STIE Jambatan Bulan, 2025)
This research aims to find out the superior potential and competitiveness of each sector in the agriculture, forestry and fisheries sectors in Aceh province and to find out what sub-sectors of agriculture, forestry and fisheries are the basic and non-basic sub-sectors in the economy in Aceh province. The sub-sectors in Aceh province are all basic sectors. This type of research is descriptive quantitative which uses time series data, namely secondary data such as GRDP data on Gross Regional Domestic Product at Constant Prices in Aceh Province. The analysis method used is Location Quetient (LQ) and Shift Share (SS) Analysis for the Agriculture, Forestry and Fisheries Sub Sector. The 5 sectors that have the highest value in the base sector in the area are the first, namely the agricultural & hunting services subsector, which the second is the horticultural crops sub-sector, the third is the livestock sub-sector, the fourth is the agriculture, livestock, hunting and agricultural services sub-sector and the fifth is the agriculture, forestry and fisheries sector. From the shift share calculations, the sub-sectors that have the greatest potential to increase economic growth are the agriculture, forestry and fisheries sub-sectors